Experimental studies on droplet formation in a flow-focusing microchannel in the presence of surfactants. (23rd February 2019) - Roumpea, Evangelia; Kovalchuk, Nina M.; Chinaud, Maxime; Nowak, Emilia; Simmons, Mark J.H.; Angeli, Panagiota
Highlights: Use of an innovative, two-colour micro-PIV technique to investigate velocity fields. Study of kinetics of surfactant absorption during the droplet formation process. Development of a mechanistic model for the droplet formation based on PIV data. Investigation of the effect of surfactants on the flow pattern maps. Abstract: The formation of an aqueous droplet in an organic continuous phase was studied experimentally inside a flow-focusing microchannel (190 μm × 195 μm: depth × width) in the presence of surfactants. A low viscosity silicone oil (0.0046 Pa s) was used as the continuous phase and a mixture of 48% w/w water and 52% w/w glycerol was the dispersed phase. Two ionic surfactants, C12 TAB (50 mM) and C16 TAB (5 mM) were added in the aqueous phase, at concentrations above the CMC values. Four regimes of drop formation were identified, namely squeezing, dripping, jetting and threading, whose boundaries changed when the surfactants were present. The drop formation process and the velocity profiles in both phases in the squeezing and dripping regimes were studied in more detail using a two-colour Particle Image Velocimetry technique. For all solutions studied, three distinct drop formation stages were identified, expansion, necking and pinch-off. The surfactant-laden solutions produced smaller drops. Considering the dynamic interfacial tension, rather than the equilibrium one, it was possible to explain differences in the drop formation between the two surfactant systems in the expansion stage. The forces acting on the forming drops were estimated and showed that the drag force overcomes the interfacial tension force at the transition between the expansion and necking stages. During this transition, the curvature of the neck changed while its thinning rate was increased. The transition from the necking to the pinch-off stage was signified by a flow reversal at the bottom part of the drop.